A comparison of dynamic warm-up and “warm-up” using self-massage tools on subsequent sit-and-reach displacement - Aquino, Michele; DiMenna, Frederick; Petrizzo, John; Yusuff, George; Otto, Robert M.; Wygand, John (PloS one, 2024)
A dynamic warm-up (DWU) comprising exercise involving rhythmic muscle actions results in an acute increase in range of motion; however, recent findings suggest that a passive one using self-massage techniques might elicit a similar effect. This study's purpose was to compare the acute effect of leg cycling DWU on sit-and-reach score to the effect of a preparatory regimen of foam rolling (FR) or percussive massage (PM). Single-blind, randomized, repeated-measures crossover study. Thirty-two asymptomatic, physically-active participants (male; n = 17) aged 20.9 ± 1.5 years performed sit-and-reach tests before, immediately following and 10-, 20- and 30-minutes following eight minutes of each of the "warm-ups." Analyses of variance at each time point across conditions and for the percent change elicited by each intervention were conducted to determine significant differences (p < 0.05). Repeated-measures ANOVA revealed a significant difference between mean percent difference of sit-and-reach score for FR (8.8 ± 0.5%) compared to DWU and PM (p = 0.046 and 0.048, respectively) while DWU (6.3 ± 0.8%) and PM (6.8 ± 0.5%) did not differ (p = 0.717). There were no differences between scores across interventions at any of the four time points. A bout of FR or PM resulted in an acute increase in a sit-and-reach score during a test performed immediately post and at 10-, 20- and 30-minutes post that was similar in magnitude to that which was present following leg cycling. These passive "warm-ups" are appropriate alternate strategies that can be employed to improve performance on a sit-and-reach test.